Role of sublingual immunotherapy in the treatment of asthma: An updated systematic review. Issue 9 (9th June 2018) - Lin, Sandra Y.; Azar, Antoine; Suarez‐Cuervo, Catalina; Diette, Gregory B.; Brigham, Emily; Rice, Jessica; Ramanathan, Murugappan; Robinson, Karen A.
Abstract : Background: The purpose of the systematic review is to evaluate the efficacy and safety of sublingual immunotherapy (SLIT) for the treatment of allergic asthma. Methods: PubMed, Embase, and CENTRAL databases were searched, updating an earlier review (January 1, 2005 through May 8, 2017). Randomized, controlled studies (RCTs) were included, which reported one of the prespecified outcomes: asthma symptoms measured by control composite scores; quality of life; medication use; pulmonary physiology; and health‐care utilization. For safety outcomes, RCTs and observational studies were included. Two independent reviewers extracted data, assessed risk of bias, and graded strength of evidence (SOE) for each outcome. Results: Fourteen RCTs (n = 2585) assessed the efficacy of SLIT for asthma. The RCTs utilized house dust mite (HDM), birch, or grass allergen. SLIT improved asthma symptoms (high SOE), decreased use of long‐term control medication, and improved forced expiratory volume in 1 second (FEV1 ) (moderate SOE). SLIT may decrease quick‐relief medication use, and improve disease‐specific quality of life (low SOE). For safety, 20 RCTs and 10 observational studies (n = 3621) were identified. Local (risk differences ranged from −0.03 to +0.765) and systemic allergic reactions (risk differences ranged from −0.03 to +0.06) were a common occurrence in SLIT and control groups. Life‐threatening reactions were uncommon, with 3 cases of anaphylaxis and no deaths reported. Conclusion: There is moderate‐to‐high strength evidence that SLIT improves allergic asthma symptoms, reduces long‐term control medication use, and improves FEV1 based on studies of HDM, birch, and grass. SLIT rarely is associated with life‐threatening adverse events.